Landscape management as a local tool for landscape protection - Illyés, Zsuzsanna (4D Journal of Landscape Architecture and Garden Art, 2015)
By the early XXI. century, our understanding of landscape has extended past the mere grasp of uniqueness, natural and cultural values and attractiveness, and now includes knowledge about vegetation, spatial structure – both constantly changing in space, time and quality – and ecological functions. As a result, the functions of landscape protection have also become more extensive and complex – today, we consider landscape to be an entity with its own identity and history, that might be damaged in several ways, but can also be developed. Spatial planning and the protection of heritage and landscape have created a system of support and protection for restricting landscape use both legally and spatially. However, within the system, there is a lack of local professionals (both as a profession and as executive employees) who can apply the knowledge, understand the framework and are able to execute plans. The landscape management programme to be launched by SzIU will focus on the following landscape protection issues.
Keywords: landscape management; landscape protection